Acoustic-emission method for controlling the defect-formation process in light-emitting structures - Lyashenko, O.V.; Vlasenko, A.I.; Veleschuk, V.P.; Kisseluk, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Сomplex researches of light-emitting structures based on А₃В₅ compounds have been carried out. It has been shown that at current loading exceeding the acousticemission threshold, there arises a change in the electroluminescence intensity, fluctuation of current and light. It has been ascertained that natural ageing leads to a general improvement of some practically important parameters of light-emitting structures, in particular to increase of maximal admissible currents and reliability.